Functional links between thermoregulation and sleep in children with neurodevelopmental and chronic health conditions - McCabe, Susan M.; Abbiss, Chris R.; Libert, Jean-Pierre; Bach, Véronique (Frontiers in Psychiatry, 2022)
The bi-directional relationship between sleep and wake is recognized as important for all children. It is particularly consequential for children who have neurodevelopmental disorders (NDDs) or health conditions which challenge their sleep and biological rhythms, and their ability to maintain rhythms of participation in everyday activities. There are many studies which report the diverse reasons for disruption to sleep in these populations. Predominantly, there is focus on respiratory, pharmaceutical, and behavioral approaches to management. There is, however, little exploration and explanation of the important effects of body thermoregulation on children’s sleep-wake patterns, and associated behaviors. Circadian patterns of sleep-wake are dependent on patterns of body temperature change, large enough to induce sleep preparedness but remaining within a range to avoid sleep disturbances when active thermoregulatory responses against heat or cold are elicited (to maintain thermoneutrality). Additionally, the subjective notion of thermal comfort (which coincides with the objective concept of thermoneutrality) is of interest as part of general comfort and associated behavioral responses for sleep onset and maintenance. Children’s thermoregulation and thermal comfort are affected by diverse biological functions, as well as their participation in everyday activities, within their everyday environments. Hence, the aforementioned populations are additionally vulnerable to disruption of their thermoregulatory system and their capacity for balance of sleep and wakefulness. The purpose of this paper is to present hitherto overlooked information, for consideration by researchers and clinicians toward determining assessment and intervention approaches to support children’s thermoregulation functions and promote their subjective thermal comfort, for improved regulation of their sleep and wake functions.